The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3149/fth.0801.131
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Depressive Symptoms and Adolescent Functioning: The Moderating Effect of Gender and Father Hostility

Abstract: This study examined the longitudinal relationship between paternal depressive symptoms, paternal hostility, and adolescent functioning in a community sample of 451 families. Paternal depressive symptoms were a strong predictor of adolescent outcome, even after controlling for family demographic variables, maternal depressive symptoms, and previous adolescent symptoms. Adolescent gender and perception of paternal hostility moderated this association such that females reporting high paternal hostility were parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 40 publications
2
44
0
1
Order By: Relevance
“…The present findings suggest, however, that it is the combination of fathers' depressive symptoms and hostile behavior that is most likely to foster social reticence in girls. These results are similar to those reported by Reeb et al (2010), who found that highly hostile fathers with depressive symptoms predicted female (but not male) adolescents' internalizing problems after controlling for maternal behavior.…”
Section: Parental Hostility and Children's Social Reticencesupporting
confidence: 89%
“…The present findings suggest, however, that it is the combination of fathers' depressive symptoms and hostile behavior that is most likely to foster social reticence in girls. These results are similar to those reported by Reeb et al (2010), who found that highly hostile fathers with depressive symptoms predicted female (but not male) adolescents' internalizing problems after controlling for maternal behavior.…”
Section: Parental Hostility and Children's Social Reticencesupporting
confidence: 89%
“…Los resultados de este estudio mostraron una correlación positiva entre ansiedad y depresión. Esto coincide con lo reportado en población general (69,70) y en cuidadores de niños con cáncer (44,46,48,71) . Además, se observó que existe una correlación de estas variables con carga, en plena coincidencia con lo informado en la literatura (1,14,24,33,53,72) .…”
Section: Discussionunclassified
“…However, Meadows et al (2007) found no significant association between paternal anxiety or depression and behaviour problems in children at three years of age. Regardless, there is agreement in the literature that there is an increased risk of emotional and behavioural problems in children when co-residential parents both experience poor mental health (Kahn et al, 2004;Meadows et al, 2007;Reeb et al, 2010;Spector, 2006). There is some evidence that poor paternal mental health may also have a negative impact on maternal mental health, both during the prenatal and postnatal periods (Field et al, 2006).…”
Section: Risk For Children's Mental Healthmentioning
confidence: 99%